2008
DOI: 10.1038/sc.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary melanotic schwannoma of the conus medullaris: a case report

Abstract: Study design: A case of a very rare type of schwannoma is reported. It is the sixth reported case of intramedullary melanotic schwannoma and the only one localized in the conus. Methods: A 56-year-old woman was treated in this department for a C5-C6 spondylodiscitis. After 6 months her arms showed a rapid recovery, but her incomplete flaccid paraplegia remained stable. Magnetic resonance imaging (MRI) with gadolinium enhancement of the lumbar tract revealed an intramedullary lesion at the level of Th12-L1. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
(9 reference statements)
0
10
0
3
Order By: Relevance
“…Regarding their recurrence potential, we found in the literature rates ranging from 18.2% 6 to 24%, 7 being almost always related to incomplete resections. [1][2][3][4]7 Moreover, studies have shown that among patients who were followed for more than five years, only slightly more than half were disease free at the end of follow-up, suggesting that long term monitoring is necessary to assess tumor recurrence and risk of metastasis. 10 …”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Regarding their recurrence potential, we found in the literature rates ranging from 18.2% 6 to 24%, 7 being almost always related to incomplete resections. [1][2][3][4]7 Moreover, studies have shown that among patients who were followed for more than five years, only slightly more than half were disease free at the end of follow-up, suggesting that long term monitoring is necessary to assess tumor recurrence and risk of metastasis. 10 …”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3][4][5][6][7][8] We found a mean age of about 50 years old, the masculine gender being present in slightly more than half of the cases reviewed. The thoracic level was the most affected, with prevalence of extramedullary location (eight of the eleven reported cases), as well as in our patient, in which we found the development of extramedullary and intradural injury.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is only the 7th reported case to our knowledge describing this tumor (Table 1). 2 , 59 Various explanations for this tumor's unusual location in the central nervous system have been put forth (Table 2). 6,8 , 1013 …”
Section: Discussionmentioning
confidence: 99%